HUBUNGAN ANTARA WORK LIFE BALANCE DENGAN STRES KERJA PADA PERAWAT DI RUANGAN ICU RSUP PERSAHABATAN JAKARTA TIMUR - Sarah Nur Chaliza (2023)
Balancing the work-life balance of nurses with the demands from inside and outside of work is difficult and can trigger work stress. The stress of these nurses has a negative impact on themselves and the organization. The research aims to determine the relationship between work-life balance and work stress in ICU nurses at Persahabatan General Hospital of East Jakarta. This study used a quantitative method with a cross-sectional design. The sampling technique used was total sampling with 61 nurses as the sample. The primary data is collected by distributing questionnaires and secondary data is obtained from hospital data. Age, gender, marital status, work period, and work-life balance are the independent variables, while work stress is the dependent variable. Data analysis performed was univariate and bivariate analysis using the chi-square test. The results showed that work period (p=0.039) and work-life balance (p=0.010) had a relationship with work stress. Meanwhile, age (p=0.754), gender (p=0.086), and marital status (p=0.743) there was no relationship with work stress. It can be concluded that work-life balance can affect the level of stress on nurses, so hospitals need to make efforts so that nurses do not experience work stress by facilitating the work-life balance of their nurses.